Elizabeth C. Banks. Lerna, a preclassical site in the Argolid, Volume VII, the Neolithic settlement - Kotsakis, Kostas (Journal of Greek Archaeology, 2016)
Among field archaeologists and excavators there has always been a firm opinion that publication of old excavations presents a real challenge requiring considerable reserves of skill and dedication. Such is the nature of research that, despite the care with which the original project has been carried out, the methodology adopted and the goals set are always intimately related to the concepts and ideas current at the time of the project. Rarely methods, which once looked cutting edge, and goals considered at their time groundbreaking will remain up to the standards of the present or preserve some of the original sophistication. Advances in the discipline and shifts of debate to other directions favour the application of a more intensive retrieval and documentation regime on a scale inconceivable even a few decades ago. Needless to say, the difficulties increase considerably when the original mastermind is not around anymore.